2014
DOI: 10.1007/s00264-014-2417-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant tumours of the scapula—a review of 29 cases

Abstract: The overall prognosis of primary malignant bone tumours of the scapula remains to be inferior compared to extremity sarcoma. Endoprosthetic reconstruction, however, shows promising functional results even in cases of total scapulectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…The shoulder girdle is comprised of the proximal humerus, scapula, clavicle and the surrounding soft tissues and is the third most common site for bone and soft tissue tumours [ 1 , 2 ]. In a report of 1853 cases of bone cancer, 3.6% ( n = 66) were found to originate from the scapula [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The shoulder girdle is comprised of the proximal humerus, scapula, clavicle and the surrounding soft tissues and is the third most common site for bone and soft tissue tumours [ 1 , 2 ]. In a report of 1853 cases of bone cancer, 3.6% ( n = 66) were found to originate from the scapula [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pritsch T et al showed that scapular prostheses, as compared with humeral suspension, had better functional results, 78.5% and 58.5% respectively, and superior cosmesis [3] . Puchner et al reported 80% in prosthesis and 58% in humeral suspension [9] . Our results were 78.6% and 71.3% which is slightly better score in humeral suspension.…”
Section: Discussionmentioning
confidence: 97%
“…However, surgical reconstruction presents a great challenge when the whole scapula is resected. Many methods, such as humeral suspension, autograft, or allograft replacement of scapula and use of scapular prosthesis, have been used for reconstruction after total scapulectomy . Of these methods, the prosthetic reconstruction is considered as the most effective method because of acceptable cosmesis, good postoperative function, and relatively low complication rate .…”
Section: Introductionmentioning
confidence: 99%
“…Many methods, such as humeral suspension, autograft, or allograft replacement of scapula and use of scapular prosthesis, have been used for reconstruction after total scapulectomy. 4,[7][8][9][10][11][12][13][14][15][16][17] Of these methods, the prosthetic reconstruction is considered as the most effective method because of acceptable cosmesis, good postoperative function, and relatively low complication rate. 3,4,[7][8][9][10][11] Generally, there are two kinds of scapular prosthesis: nonconstrained and constrained.…”
Section: Introductionmentioning
confidence: 99%